Genetic Manipulation Strategies for β-Thalassemia: A Review - Nur Atikah Zakaria; Rosnah Bahar; Wan Zaidah Abdullah; Abdul Aziz Mohamed Yusoff; Shaharum Shamsuddin; Shaharum Shamsuddin; Shaharum Shamsuddin; Ridhwan Abdul Wahab; Muhammad Farid Johan (Frontiers Media S.A., 2022)
Thalassemias are monogenic hematologic diseases that are classified as α- or β-thalassemia according to its quantitative abnormalities of adult α- or β-globin chains. β-thalassemia has widely spread throughout the world especially in Mediterranean countries, the Middle East, Central Asia, India, Southern China, and the Far East as well as countries along the north coast of Africa and in South America. The one and the only cure for β-thalassemia is allogenic hematopoietic stem cell transplantations (HSCT). Nevertheless, the difficulty to find matched donors has hindered the availability of this therapeutic option. Therefore, this present review explored the alternatives for β-thalassemia treatment such as RNA manipulation therapy, splice-switching, genome editing and generation of corrected induced pluripotent stem cells (iPSCs). Manipulation of β-globin RNA is mediated by antisense oligonucleotides (ASOs) or splice-switching oligonucleotides (SSOs), which redirect pre-mRNA splicing to significantly restore correct β-globin pre-mRNA splicing and gene product in cultured erythropoietic cells. Zinc finger nucleases (ZFNs), transcription activator-like effector nucleases (TALENs) and clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated 9 (Cas9) are designer proteins that can alter the genome precisely by creating specific DNA double-strand breaks. The treatment of β-thalassemia patient-derived iPSCs with TALENs have been found to correct the β-globin gene mutations, implying that TALENs could be used as a therapy option for β-thalassemia. Additionally, CRISPR technologies using Cas9 have been used to fix mutations in the β-globin gene in cultured cells as well as induction of hereditary persistence of fetal hemoglobin (HPFH), and α-globin gene deletions have proposed a possible therapeutic option for β-thalassemia. Overall, the accumulated research evidence demonstrated the potential of ASOs-mediated aberrant splicing correction of β-thalassemia mutations and the advancements of genome therapy approaches using ZFNs, TALENs, and CRISPR/Cas9 that provided insights in finding the permanent cure of β-thalassemia.